Salutary Effects of Overexpression of Rsm22, an Assembly Factor for the Mitochondrial Ribosome, on Frataxin/Yfh1 Depletion Phenotypes in Saccharomyces cerevisiae - Ashutosh K. Pandey; Pratibha Singh; Jayashree Pain; Andrew Dancis; Debkumar Pain (Biomolecules, 2025)
Frataxin is a component of the iron–sulfur (Fe-S) cluster assembly complex in mitochondria, and deficiency is associated with Friedreich ataxia (FA). The yeast homolog Yfh1 resembles and cross-complements with its human equivalent, and frataxin bypass scenarios are of particular interest because they may point to strategies for treating FA. Here, we describe frataxin/Yfh1 bypass by overexpression of Rsm22, an assembly factor for the mitochondrial ribosome. Rsm22 overexpression in Yfh1-depleted yeast cells restored critical processes in mitochondria, including Fe-S cluster assembly, lipoic acid synthesis, iron homeostasis, and heme synthesis, to a significant extent. Formation of cytoplasmic Fe-S proteins was also restored, suggesting recovery of the mitochondrial ability to generate the (Fe-S)int intermediate that is exported from mitochondria and is utilized for cytoplasmic Fe-S cluster assembly. Importantly, an essential component of the mitochondrial iron–sulfur cluster machinery, namely ferredoxin, was virtually absent in mitochondria lacking Yfh1, but it was recovered with Rsm22 overexpression. Interestingly, ferredoxin overexpression could offset some of the effects of Yfh1 depletion. Ferredoxin has recently been shown to bind to the cysteine desulfurase protein Nfs1 at the same site as Yfh1, in a conserved arginine patch on Nfs1, such that ferredoxin binding at this site may confer frataxin-bypass activity.